The Effects of Wave Spectrum on Spar Platform - Mohd Redzuan Bin Abdan, Mohd Redzuan (Universiti Teknologi Petronas, 2009)
Deep draft spar platforms have been regarded as competitive alternative structure for deepwater oil field development. Spar platform is a freely floating structure and subjected to 3 main hydrodynamic motions that are surge, heave and pitch. In order to determine the hydrodynamic motion responses of spar platform during deepwater operation, numerical studies can be conducted. In numerical simulations there two main approaches,that are time domain analysis and frequency domain analysis. This report contains analysis of it spar platform in frequency domain analysis.The frequency-domain technique is simpler and faster than the time-domain approach and requires fewer computing resources